Crossing the Threshold of Temporality: "Story of Your Life" and Arrival - Chiara Patrizi (Università degli Studi di Torino, 2020)
In Denis Villeneuve’s 2016 science-fiction movie, Arrival, the world is disrupted by the sudden arrival of a fleet of alien spaceships, an event that is going to challenge human conceptions of time, language, and free will. The movie is based on Ted Chiang’s 1998 novella "Story of Your Life," and both the original text and its film adaptation deal with understanding and coming to terms with otherness—alien language, time, death, grief—through the encounter of human and extraterrestrial existence and the exploration of the threshold that connects (or separates) life and afterlife. This essay examines the ways in which the novella and the film address the modes of the weird and the eerie, two concepts which have been theorized by Mark Fisher as “the presence of that which does not belong” and “a failure of absence or a failure of presence” respectively. These modes offer a key to analyzing and understanding the strategies that Chiang and Villeneuve employ to narrate a two-fold story which affects the communal as well as the individual existence. With its ostensibly impossible language, such story bears a significance that lies beyond and outside human perception. "Story of Your Life" deals with the “out of”—that outer dimension which lies beyond our experience of the categories of time and space (Fisher 24-25), not necessarily from a scientific perspective but rather from an existential one. Thus, the heptapods’ arrival raises questions (Why are they here? What do they want?) and poses challenges (How can we speak to them?)  which open the way for other, more existential questions and challenges. Eventually, failure of absence (the appearance of the spaceships) and failure of presence (the death of the daughter of the protagonist) meet here, and their encounter provides a powerful meditation on the eerie feelings that haunts human agency and affects our understanding of reality.